Upaya Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Menggunting Pola - Azurah Azurah; Mohammad Fauziddin; Nurmalina Nurmalina (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study aims to improve fine motor skills of early childhood through pattern cutting activities in group B children at Tunas Harapan Kindergarten. The research method used was classroom action research conducted in 2 cycles. The research subjects were 14 children in group B TK Tunas Harapan. The object of his research is pattern cutting activities and fine motor skills of early childhood. The data analysis used is percentage. The data taken is in the form of end-of-cycle test results and direct work results. The results showed that the fine motor skills of early childhood through cutting patterns developed very well in each indicator. The results can be seen in the action cycle II. Where the indicator for children being able to hold scissors correctly gets a score of 85,71%, the indicator for children being able to cut according to a pattern gets a score of 92.86%, the neat cutting indicator gets a score of 78.57%. as well as the indicator of children being able to cut out imitating the shape of a picture gets a value of 92.86%. Keywords: Fine Motor Skills, Cutting Patterns, Classroom action research